Multifrequency studies of galaxies and groups I. Environmental effect on galaxy stellar mass and morphology - Poudel A; Heinamaki P; Nurmi P; Teerikorpi P; Tempel E; Lietzen H; Einasto M (EDP SCIENCES S A, 2022)
Context. To understand the role of the environment in galaxy formation, evolution, and present-day properties, it is essential to study the multifrequency behavior of different galaxy populations under various environmental conditions.Aims. We study the stellar mass functions of different galaxy populations in groups as a function of their large-scale environments using multifrequency observations.Methods. We cross-matched the SDSS DR10 group catalog with GAMA Data Release 2 and Wide-field Survey Explorer (WISE) data to construct a catalog of 1651 groups and 11 436 galaxies containing photometric information in 15 different wavebands ranging from ultraviolet (0.152 mu m) to mid-infrared (22 mu m). We performed the spectral energy distribution (SED) fitting of galaxies using the MAGPHYS code and estimate the rest-frame luminosities and stellar masses. We used the 1/V-max method to estimate the galaxy stellar mass and luminosity functions, and the luminosity density field of galaxies to define the large-scale environment of galaxies.Results. The stellar mass functions of both central and satellite galaxies in groups are different in low-and high-density, large-scale environments. Satellite galaxies in high-density environments have a steeper low-mass end slope compared to low-density environments, independent of the galaxy morphology. Central galaxies in low-density environments have a steeper low-mass end slope, but the difference disappears for fixed galaxy morphology. The characteristic stellar mass of satellite galaxies is higher in high-density environments and the difference exists only for galaxies with elliptical morphologies.Conclusions. Galaxy formation in groups is more efficient in high-density, large-scale environments. Groups in high-density environments have higher abundances of satellite galaxies, irrespective of the satellite galaxy morphology. The elliptical satellite galaxies are generally more massive in high-density environments. The stellar masses of spiral satellite galaxies show no dependence on the large-scale environment.